Integrative levels : - Needham, Joseph (The Clarendon press, 1937)
An integrative level, or level of organization, is a set of phenomena emerging on pre-existing phenomena of lower level. Typical examples include life emerging from non-living substances, and consciousness emerging from nervous systems.